FRI0224 Predictive factors of response to tocilizumab in patients with active rheumatoid arthritis. (23rd January 2014) - Reina, D.; Narvaez, J.; García-Díaz, S.; Díaz Torné, C.; Magallares, B.; Hernandez, M. V.; Sanmartí, R.; Rodriguez de la Serna, A.; Llobet, J.; Corominas, H.; Nolla, J.
Abstract : Objectives: To evaluatethe efficacy and identify predictors of response to tocilizumab (TCZ) in patients with rheumatoid arthritis. Methods: A multi-center ambispective observational study in 126 patients with active rheumatoid arthritis treated with TCZ. The variables associated to achieve the therapeutic goal (remission of the disease defined as a DAS28 <2.6) at 3 and 6 months, were identified by a logistic regression model by using the backward approach. SAS 9.3 was used for the management and statistical analysis. Results: Patients' demographic and clinical characteristics are shown in table 1, as well as response rates at 3 and 6 months of treatment. Of the 126 patients included, TCZ was administered as first biologic in 33 cases (26%), while in the remaining 93 patients was used after inadequate response (inefficacy or intolerance) to one or more biological therapies (the average of previous biological drugs tested per patient was 2.18 ±1.1, range 1-6). Only 43 (35%) patients received TCZ as monotherapy. Of all the variables analyzed by the multivariate analysis, the predictive factors that increase the likelihood of response DAS28-ESR 2.6 to 3 months were ESR> 30 mm / h (OR=19.07, 95% CI: 2.7, 133.7) and the presence of extra-articular manifestations of the disease (OR = 15.5, 95% CI 2.3, 102.3). Factors that decreased it were hemoglobin (OR = 0.53, 95% CI: 0.32, 0.91), the baseline DAS28-ESR (OR = 0.30, 95% CI: 0.15, 0.64) and the number of previous DMARDs used (OR = 0.42, 95% CI: 0.22, 0.78). The only significant factor that reduced the possibility of DAS28-ESR response <2.6 at 6 months was the baseline DAS28-ESR (OR = 0.55, 95% CI: 0.35, 0.88). No relationship was found in the number of previous biological therapies, nor in the decrease of the neutrophils count nor in the positivity RF/anti-PCC. Conclusions: Some clinical and laboratory variables can help in the selection of the best candidates for treatment with tocilizumab. Disclosure of Interest : None Declared